Self-Regulated Learning and Epistemological Belief as Determining Factors of Success in English Learning - Mazaya Ishma Karamina; Tari Ariska (CV. Akademi Merdeka, 2025)
This study explores the role of Self-Regulated Learning (SRL) and Epistemological Beliefs (EB) in influencing students' English language proficiency in Indonesian universities. Using a quantitative research design, data were gathered from 246 students through validated questionnaires, including the Motivated Strategies for Learning Questionnaire (MSLQ) and the Epistemological Beliefs Questionnaire (EBQ). The results of multiple regression analysis show that both SRL and EB significantly affect English ability. Students with higher levels of self-regulation and more advanced epistemological beliefs demonstrated better performance in reading, writing, speaking, and listening. These findings highlight that English proficiency is influenced not only by cognitive factors but also by motivational and metacognitive elements. The study emphasizes the need to integrate self-regulation strategies and the development of epistemological beliefs into English language instruction. This research contributes to learner-centered education by providing insights into how internal factors can support more effective English learning outcomes.